Geological structure and landscapes of the Dvorichanskyi National Nature Park - Космачова, М. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
Dvorichanskyi National Park is located in the north-eastern part of Kharkiv region in the southern part of the Voronezhska Anteclise of the East European Platform. The geological landmarks of this region were described. There are some stratigraphical objects with the Upper Cretaceous writing chalk and marls in this locality. The geological landmarks of this park have large scientific and educational meaning. They are very important for characterizing the geological structure of the North-East Ukraine.